RELIGIUSITAS DAN MATERIALISM TERHADAP PENGGELAPAN PAJAK DENGAN LOVE OF MONEY SEBAGAI VARIABEL MODERASI - Herman Ernandi; Fityan Noor Izzah; Syaidah Rohmatul Ummah (Owner : Riset dan Jurnal Akuntansi, 2023)
The purpose of conducting a study in this study was to determine the effect of religiosity and materialism on tax evasion with love of money as a moderating variable (study of the Indonesian Association of Electrical and Mechanical Contractors, Sidoarjo Branch Management Council). The population taken in this research was members of the Indonesian Electrical and Mechanical Contractors Association, the Management Board of the Sidoarjo Branch. Probability sampling or random sampling is used by distributing questionnaires and getting 50 respondents. Then the primary data which is the source of data in this study were analyzed using the Outer Model to test the validity and reliability of the data. Furthermore, it also uses the Inner Model to test hypotheses and data is processed with the help of the smartPLS version 3.0 program. According to the results of the hypothesis test, it shows that the religiosity variable has a significant effect on tax evasion, but the materialism variable has no effect. In moderation, love of money is not able to moderate the religiosity variable, but love of money is said to be able to moderate the materialism variable on tax evasion.